Water yield response to forest treatment patterns in a sierra nevada watershed - Katy A. Smith; Katie E. Schneider; Alicia M. Kinoshita; Jake Kurzweil; Bob Prucha; Terri S. Hogue (Journal of Hydrology: Regional Studies, 2024)
Study region: Sierra Nevada Study focus: Snow dominated forests serve as source water supplies to much of the western United States. In recent years, these forests have experienced an increase in both drought and wildfire, which threaten critical water resources. By reducing forest density, treatments offer a promising solution to reducing fuel loads and potentially increasing surface water yield. However, the amount of fuel load reduction necessary to produce a change in water yield is not well-characterized. The objectives of the current study are to: 1) calibrate a distributed parameter, fully-integrated and physically-based hydrologic model to available watershed data and evaluate predicted hydrologic changes for a range of fuel treatment scenarios in a heavily forested experimental basin in the Sierra Nevada (Sagehen Creek basin near Truckee, California, USA), and 2) determine the extent (threshold) of forest treatments necessary to produce substantial changes, i.e. a 25% increase, in surface runoff. New hydrological insights for the region: Using DHI’s physically-distributed code, MIKESHE, to develop the model for Sagehen Basin, twenty forest treatment scenarios with varying canopy density reductions (CDRs) and areas of treatment were simulated for a five-year period. Statistical testing showed that significant change in runoff occurred for every developed scenario at the annual scale (99% confidence interval). Surface water yield is highly correlated with precipitation patterns, however, treatments have a compounding effect over the years and the basin has a more dramatic response to higher treatment intensities. Increasing treatment CDR was more effective at increasing water yield than increasing treatment area. Results suggest that as forest managers implement fuel treatments, water yield response depends on: 1) the degree to which treatments are implemented by either area or CDR, 2) future climate variability including extended periods of drought, and 3) basin storage conditions and how this might buffer disturbance response in the basin.